2009
DOI: 10.1097/mph.0b013e3181984d91
|View full text |Cite
|
Sign up to set email alerts
|

Nifurtimox Induces Apoptosis of Neuroblastoma Cells In Vitro and In Vivo

Abstract: Neuroblastoma is the most common extracranial solid tumor in children and, when disseminated, carries a poor prognosis. Even with aggressive combinations of chemotherapy, surgery, autologous bone marrow transplant and radiation, long-term survival remains at 30% and new therapies are needed. Recently, a patient with neuroblastoma who acquired Chagas disease was treated with nifurtimox with subsequent reduction in tumor size. The effect of nifurtimox on the neuroblastoma cell lines CHLA-90, LA1-55n, LA-N2, SMS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 17 publications
3
38
0
1
Order By: Relevance
“…Nifurtimox is a nitrofuran compound that has been used since the 1970s as a primary form of therapy for Chagas' disease, a parasitic infection caused by Trypanosoma cruzi [132,133]. Preclinical studies have shown that nifurtimox inhibits neuroblastoma cell growth in vitro and in vivo [134,135], and in early-phase clinical trials tumor responses were seen in patients treated with nifurtimox at a dose of 30 mg/kg/day both as a single agent and in combination with chemotherapy [136], leading to an ongoing national phase II trial (NCT00601003).…”
Section: Treatment -Relapsed and Refractory Neuroblastomamentioning
confidence: 99%
“…Nifurtimox is a nitrofuran compound that has been used since the 1970s as a primary form of therapy for Chagas' disease, a parasitic infection caused by Trypanosoma cruzi [132,133]. Preclinical studies have shown that nifurtimox inhibits neuroblastoma cell growth in vitro and in vivo [134,135], and in early-phase clinical trials tumor responses were seen in patients treated with nifurtimox at a dose of 30 mg/kg/day both as a single agent and in combination with chemotherapy [136], leading to an ongoing national phase II trial (NCT00601003).…”
Section: Treatment -Relapsed and Refractory Neuroblastomamentioning
confidence: 99%
“…Additionally, some T. cruzi strains are reported to be refractory to treatment (17,37). Despite these problems, nifurtimox, in cotherapy with eflornithine (NECT), has recently been added to the WHO's Essential Medicines List for treatment of West African trypanosomiasis (8,(42)(43)(44), and it is currently being subjected to clinical trials as a treatment for pediatric neuroblastoma (47,48).…”
mentioning
confidence: 99%
“…Igualmente y dado que el nifurtimox está siendo evaluado como medicamento en el tratamiento de algunos canceres como neuro y meduloblastoma, su actividad antitumoral ha sido demostrada en diferentes tipos de células cancerosas (30). Ensayos in vitro en líneas celulares de neuroblastoma mostraron ligeras diferencias en la toxicidad al nifurtimox siendo más susceptibles las que presentaban mayor producción de ROS (31). Se demostró además que el nifurtimox inducía apoptosis en células de neuroblastoma y en células xenotransplantadas en ratones desnudos (31).…”
Section: Discussionunclassified